Pemberdayaan Perempuan Pelaku Usaha Kuliner Rumahan Menuju Kemandirian Ekonomi - Robi Santoso; Fatma Afriyani; Riski Eka Lestari; Ilham Setio Wibowo; Denny Kurniawan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This community service program aimed to strengthen the economic independence of women operating home-based culinary businesses in Tambah Subur Village, Way Bungur District, East Lampung Regency. The program adopted a Participatory Action Research (PAR) approach involving 25 housewives through participatory observation, collaborative planning, production training, business management and digital marketing assistance, as well as monitoring and evaluation. The results indicated improved participant capacity in processing local food products, maintaining simple bookkeeping, calculating production costs, and utilizing social media for product promotion. Approximately 70% of participants adopted digital branding strategies, while average household income increased by 25–30% compared with pre-program conditions. The program also facilitated the establishment of a joint business group, strengthened local female leadership, and enhanced participants' awareness of their economic potential. These findings demonstrate that the PAR approach effectively promotes sustainable economic empowerment and supports the long-term development of women-led home-based culinary enterprises.